Momentum in Corporate Bond Returns - Jostova, Gergana; Nikolova, Stanislava; Philipov, Alexander; Stahel, Christof W. (Review of Financial Studies, 2013)
This paper documents significant momentum in a comprehensive sample of 81, 491 U.S. corporate bonds with both transaction and dealer-quote data from 1973 to 2011. Momentum is driven by noninvestment grade (NIG) bonds. Momentum profits have increased over time, along with the growth of this segment. From 1991 to 2011, they average 59 basis points (bps) per month across all bonds and 192 bps in NIG bonds. NIG bonds issued by private firms earn even higher profits (282 bps). Momentum profits do not appear to compensate for risk or persist as a result of trading frictions. Bond momentum is not just a manifestation of equity momentum. The Author 2013. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.